Heads up : changing minds on mental health - Siebert, Melanie (Orca Book Publishers, 2020)
Explores mental health and mental illnesses, discussing its history, different treatments, trauma, and recovery. Includes real-life stories of people who deal with mental health issues and tips and resources for getting help and thriving.